Near-edge X-ray absorption fine structure spectroscopy and structural properties of Ni-doped CeO2 nanoparticles. Issue 11 (2nd December 2017) - Kumari, Kavita; Vij, Ankush; Chae, K. H.; Hashim, Mohd.; Aljawfi, Rezq Naji; Alvi, P. A.; Kumar, Shalendra
ABSTRACT: Ni-doped CeO2 nanoparticles were prepared by using the co-precipitation method. The prepared nanoparticles were characterized using X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, Raman spectroscopy, field emission scanning electron microscopy (FE-SEM) and near-edge X-ray absorption fine structure (NEXAFS) spectroscopy. The XRD results infer that Ni-doped CeO2 nanoparticles have single phase nature similar to that of pure CeO2 nanoparticles. We have calculated lattice parameters using Powder-X software, particle size using Scherer's formula and strain using the Williamson-Hall method for all the synthesized samples. We have observed a systematic decrease in the lattice parameters, particle size and strain with an increase in Ni doping in CeO2 . The FE-SEM micrographs also confirm that Ni-doped CeO2 have nanocrystalline behavior and particles are spherical shaped. From the Raman spectra, it is observed that the intensity of classical CeO2 vibration modes first increases then decreases with Ni doping. The NEXAFS spectra measured at Ce M 4, 5 and Ni L 3, 2 edges clearly indicate that Ce ions are in the +4 valence state and Ni ions are in the +2 valence state.